Խոսակցական լեզվում գալ, տալ, լալ բայերի ձևերի ս-ի անկման պատճառների մասին - Գրիգորյան, Գ. Գ.
В современном разговорном языке ярким примером выпадения звуков является падение звука -ս [s]окончания -իս [is] глаголов գալիս [galis] и տալիս [talis]. Согласно нашим экспериментальным наблюдениям, звук -ս [s]в конце слова является довольно «стабильным» звуком, и мы не можем подтвердить тот факт, что спад произошел из-за слабого произношения. Падение звука «s» окончания «is» в разговорном языке обусловлено в основном принципом экономии, и в этом случае мы не имеем смысловой потери. In the modern colloquial language a striking example of falling sounds is the omission of the soundս [s] in the ending -իս [is] of the verbs գալիս [galis] and տալիս [talis]. According to our experimental observations, the soundս [s] at the end of a word is a fairly “stable” sound, and we cannot confirm the fact that the omission or the loss occurred due to weak pronunciation. The fall of the sound “s” of the ending “is” in the colloquial language is due to mainly the principle of economy, in which case we have no semantic loss.
Keywords: Լեզվաբանություն